Innovative Approaches for PCB Image Reconstruction: Tailored Datasets, Metrics, and Models - Qianyue Wang (IEEE Access)
The reconstruction of PCB (Printed Circuit Board) images is vital for quality control in electronic manufacturing, enabling fault analysis, reverse engineering, and repair. However, this task faces significant challenges due to the high complexity and precision required, compounded by densely packed layouts and image degradation from physical damage, contamination, low-light conditions, or tampered components. Existing methods often fall short due to the lack of specialized datasets, insufficient validation against real-world degradation, limited robustness to diverse defect scenarios, and evaluation metrics that fail to capture the fine details critical for PCB functionality. To address these challenges, this study introduces a data-centric approach for PCB image reconstruction, featuring three major contributions: 1) A rigorously validated dataset, PCB_Reconstruction, comprising three subsets—PCB_Mask, PCB_Blur, and PCB_Replace—systematically simulates physical damage, contamination effects, and tampered components. The dataset’s realism is validated through Structural Similarity Index Measure (SSIM) analysis and a CNN-based classification test, confirming its alignment with real-world PCB defects. 2) A new evaluation metric, Detail Reconstruction Quality (DRQ), designed to measure edge reconstruction precision, addressing the limitations of traditional metrics like PSNR and MSE. The validity of DRQ is further demonstrated by benchmarking it against SSIM and PSNR on diverse datasets, including DIV2K and Kodak, where DRQ achieves superior fine-detail reconstruction performance. 3) Comprehensive benchmarking across seven models, providing a robust evaluation of both traditional and state-of-the-art approaches. Among these, the Non-Autoregressive Transformer (NAT) stands out for its lightweight architecture and superior edge restoration performance, achieving a 11.2% DRQ improvement over U-Net on PCB_Mask and a 9.8% DRQ increase over MAE on PCB_Blur. Retraining traditional models (e.g., U-Net and EDSR) on the PCB_Reconstruction subsets further enhances DRQ scores by an average of 15%, demonstrating the dataset’s capacity to improve robustness and generalization. Experimental results confirm that the proposed datasets, evaluation framework, and benchmarking approach significantly advance the precision and reliability of PCB image reconstruction. The datasets, evaluation metrics, and results will be made publicly available at https://github.com/Wangq180/PCB_Research.